Are the minimally invasive techniques the new gold standard in thymus surgery for myasthenia gravis? Experience of a reference single-site in VATS thymectomy - Trujillo Reyes, Juan Carlos; Martinez Tellez, Elisabeth; Belda Sanchis, Josep; Planas Canovas, Georgina; Libreros Niño, Alejandra; Guarino, Mauro; Hernández Ferrandez, Jorge; Moral Duarte, Antonio (Frontiers in Neurology, 2024)
The thymus is the primary lymphoid organ responsible for the maturation and proliferation of T lymphocytes. During the first years of our lives, the activation and inactivation of T lymphocytes occur within the thymus, facilitating the correct maturation of central immunity. Alterations in the positive and negative selection of T lymphocytes have been studied as the possible origins of autoimmune diseases, with Myasthenia Gravis (MG) being the most representative example. Structural alterations in the thymus appear to be involved in the initial autoimmune response observed in MG, leading to the consideration of thymectomy as part of the treatment for the disease. However, the role of thymectomy in MG has been a subject of controversy for many years. Several publications raised doubts about the lack of evidence justifying thymectomy’s role in MG until 2016 when a randomized study comparing thymectomy via sternotomy plus prednisone versus prednisone alone was published in the New England Journal of Medicine (NEJM). The results clearly favored the group of patients who underwent surgery, showing improvements in symptoms, reduced corticosteroid requirements, and fewer recurrences over 3 years of follow-up. In recent years, the emergence of less invasive surgical techniques has made video-assisted or robotic-assisted thoracoscopic (VATS/RATS) thymectomy more common, replacing the traditional sternotomy approach. Despite the increasing use of VATS, it has not been validated as a technique with lower morbidity compared to sternotomy in the treatment of MG. The results of the 2016 trial highlighted the benefits of thymectomy, but all the patients underwent surgery via sternotomy. Our hypothesis is that VATS thymectomy is a technique with lower morbidity, reduced postoperative pain, and shorter postoperative hospital stays than sternotomy. Additionally, VATS offers better clinical improvement in patients with MG. The primary objective of this study is to validate the VATS technique as the preferred approach for thymectomy. Furthermore, we aim to analyze the impact of VATS thymectomy on symptoms and corticosteroid dosage in patients with MG, identifying factors that may predict a better response to surgery.